Pertumbuhan dan Hasil Kacang Hijau dengan Perlakuan Pupuk Kandang Ayam dan Pupuk Organik Cair (POC) Kulit Pisang di Tanah Berpasir - Budi Cahyono; Hidayati, Nurul; Saijo, Saijo (Rawa Sains: Jurnal Sains STIPER Amuntai, 2025)
Green beans are one type of food crop as a source of vegetable protein that has advantages in terms of agronomy and economy compared to other beans. The study aims to determine the effect of chicken manure, banana peel LOF and the interaction of the two treatment factors on the growth and yield of green beans in sandy soil. Held in September 2024-December 2024 at Jl. Aggrek, Gang Damai, UMPR Campus II Complex, Kereng Bangkirai Village, Sebangau District, Palangka Raya City, Central Kalimantan. The study used a factorial Randomized Block Design (RBD) with 3 replications and 2 treatment factors, the first treatment: chicken manure with 3 levels: 10, 15, 20 t ha-1 while the second factor was the provision of banana peel LOF concentration with 3 levels, namely a dose of 40 ml LOF / 200 ml of planting water, 60 ml LOF / 200 planting water, 80 ml LOF / 200 ml of planting water. The results showed that the treatment of chicken manure had a significant effect on growth variables in the form of plant height and number of leaves and had a significant effect on the yield variable in the form of dry seed weight per planting. While the treatment of banana peel LOF had an effect on the growth variables of plant height and number of leaves and had an effect on the yield variable in the form of the weight of 100 dry seeds. Furthermore, the interaction of the two factors of chicken manure and banana peel LOF treatment had a significant effect on the yield variable, namely the variable of dry seed weight per planting.